Nilai Moral dan Budaya dalam Cerita Rakyat Sakera dari Pasuruan - Pradicta Nurhuda; Novi Anoegrajekti; Siti Gomo Attas (Badan Pengembangan dan Pembinaan Bahasa, 2021)
Sakera was a figure whom the people of Pasuruan loved in his day because he opposed the injustices committed by the Dutch on the workers. However, his struggle to defend the weak turns out his love was betrayed by Brodin who had an affair with his wife. This study aims to (1) describe the moral values in the Sakera folklore, (2) describe the cultural values in the Sakera folklore. This research is a qualitative descriptive study. The data source in this study is the Sakera folklore published on the Pasuruan Regency website. The object of this research is the moral values and cultural values of Sakera folklore. Data collection techniques were carried out by reading and note-taking techniques. Checking the validity of the data used in this study is by diligently reading and taking notes and checking the validity of reference stories through published folklore. The results of this study indicate that (1) the moral values found in the Sakera folklore are (a) the value of tolerance, (b) the value of discipline, (c) the value of hard work, (d) the value of independence, (e) the value of democracy, (f) ) curiosity value, (g) friendly value, (h) social care value, and (i) responsibility value; (2) the cultural values found in the Sakera folklore are (a) philosophical values, (b) the value of patience, (c) the value of togetherness (solidarity), (d) the value of courage, and (e) the value of firm stance. AbstrakSakera merupakan sosok yang sangat dicintai rakyat Pasuruan di zamannya karena dia menentang ketidakadilan yang dilakukan oleh Belanda kepada buruh. Namun, di balik perjuangannya membela kaum lemah, ternyata cintanya dikhianati oleh Brodin yang berselingkuh dengan istrinya. Penelitian ini bertujuan (1) mendeskripsikan nilai moral dalam cerita rakyat Sakera, (2) mendeskripsikan nilai budaya dalam cerita rakyat Sakera. Penelitian ini merupakan penelitian deskriptif kualitatif. Sumber data dalam penelitian ini adalah cerita rakyat Sakera yang dimuat dalam situs laman Pemerintah Kabupaten Pasuruan. Objek penelitian ini adalah nilai moral dan nilai budaya cerita rakyat Sakera. Teknik pengumpulan data dilakukan dengan teknik baca dan teknik catat. Pengecekan keabsahan data yang digunakan dalam penelitian ini adalah dengan ketekunan membaca dan mencatat serta mengecek kevalidan cerita referensi melalui cerita rakyat yang sudah dipublikasi. Hasil penelitian ini menunjukkan bahwa (1) nilai moral yang ditemukan dalam cerita rakyat Sakera adalah (a) nilai toleransi, (b) nilai disiplin, (c) nilai kerja keras, (d) nilai mandiri, (e) nilai demokratis, (f) nilai rasa ingin tahu, (g) nilai bersahabat, (h) nilai peduli sosial, dan (i) nilai tanggung jawab; (2) nilai budaya yang ditemukan dalam cerita rakyat Sakera adalah (a) nilai filosofis, (b) nilai kesabaran, (c) nilai kebersamaan (solidaritas), (d) nilai keberanian, dan (e) nilai teguh pendirian.